The study of mitral valve annular dimension in relation to the body surface area in the Indian population - Rajila Rajendran, Hannah Sugirthabai; Seshayyan, Sudha; Victor, Ashok; Murugesan, Nirmaladevi; Sundaramurthi, Indumathi (European journal of cardio-thoracic surgery, 2011)
Objective: We compare the mitral valve annular dimension in relation to the body surface area of the Indian population as against the standard values. Methods: The study was conducted between September 2004 and February 2006 on 406 subjects, out of which 252 were males and 154 were females. A spatially oriented B-mode scan echocardiogram was used, with the long-axis plane running parallel to the heart or the left ventricle, the short-axis plane being perpendicular to the long axis, and the four-chamber plane orthogonal to the other two and somewhat representing a frontal plane. Mitral valvular dimensions were recorded in early diastole. Results: The mitral valve showed a steady rise in its diameter with rise in body surface area. For body surface area ranging from 0.61 to 0.7 m2, the mitral valve diameter was 15.5 mm. There was a sudden increase from 15.5 mm to 18 mm for body surface area ranging from 0.71 to 0.8 m2. After this sudden increase, the mitral valve diameter steadily increased by 0.2-0.6 mm for every 0.1 m2 increase in body surface area. The values obtained from the Indian population were definitely lower than the lower end of standard deviation of the standard values, which are derived in relation to body surface area. Conclusions: Although the annular dimensions of the mitral valve increased correspondingly with body surface area, they still remained very low in the Indian population as compared with the standard values, which might cause patient-prosthesis mismatch during mitral-valve replacement surgeries.